PERAN SOCIAL MEDIA ORIENTATION UNTUK MENINGKATKANINNOVATION PERFORMANCE PADA SEKTOR EKONOMI KREATIF GROBOGAN DI ERA PASCA PANDEMI COVID-19 - Indah rahayu; Dita Prameswari (JMBPreneur: Jurnal Manajemen, Bisnis, dan Kewirausahaan, 2023)
Background : The spread of the COVID-19 pandemic has entered a transitional stage after the COVID-19 pandemic. The phenomenon of increasing active use of social media among the public during the COVID-19 pandemic can be an opportunity for creative economy sector actors. With the COVID-19 pandemic which has caused all activities to be carried out in a limited way only at home, this has changed business activities towards digitalization using social media. The use of social media by creative economy actors (ekraf) is the main focus during the COVID-19 pandemic because it is able to increase the innovation performance of creative economy sector actors with the support of altruistic knowledge donating and knowledge creation.Purpose: The purpose of this study is to examine more deeply the concept of social media orientation towards innovation performance through altruistic knowledge donating and knowledge creation among creative economy actors in the Grobogan district after the COVID-19 pandemic..Methods: This research is a quantitative research using the sampling method is using purposive sampling technique. The population in this study were 187 creative economy actors, while the sample in this study was 135 samples. The data collection method in this study used a questionnaire.Conclusion: From the results of the study it can be concluded that social media orientation has a significant effect on altruistic knowledge donating, social media orientation has a significant effect on knowledge creation, altruistic knowledge donating has a significant effect on innovation performance and knowledge creation has a significant effect on innovation performance.Suggestion: For future agendas,this research can still be developed further for further research agendas by developing a model by adding the absortive capacity variable that can influence social media orientation and altruistic knowledge donating